Effective Communication as a Tool for Achieving Organizational Goal and Objective - Hamkar, Nasir Ahmad; Bashar, Hanifullah; Hikmat, Hikmatullah (Journal for Research in Applied Sciences and Biotechnology, 2024)
Effective communication is essential for providing users with the information needed to achieve specific goals. This study explores the impact of effective communication on organizational performance, focusing on efficiency and profitability. The primary research question investigates the overall influence of effective communication on organizational goals. Sub-questions examine its effects on organizational efficiency and profitability. The main hypothesis posits that effective communication enhances organizational goal attainment, while sub-hypotheses suggest it improves efficiency and profitability. Objectives include understanding the impact of effective communication on organizational goals, efficiency, and profitability. Using purposive sampling, the study involved 40 employees. Secondary data were gathered from previous journals and books. The findings indicate that effective communication contributes to organizational development by enhancing employee productivity through verbal communication, improving performance efficiency through visual communication, and facilitating quick and accurate daily activities. Furthermore, effective communication aids in providing superior customer service, increasing the effectiveness of information systems, and maximizing employee performance benefits within the organization.